ANALYSIS OF THE APPLICATION OF PSAK 106 AT BPRS HAJI MISKIN PANDAI SIKEK, TANAH DATAR REGENCY - Tartilla Devy (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
This study is prompted by the fact that musyarakah financing has not yet been fully implemented in Islamic financial institutions. Clarification is required for recognition, measurement, presentation, and accounting disclosure. The implementation of the musyarakah contract is still hampered by a number of practical issues, which should be rectified in order to meet its aims. This study attempts to assess if the BPRS Haji Miskin records musyarakah funding transactions in line with PSAK 106. This qualitative descriptive research describes the implementation of PSAK 106 at BPRS Haji Miskin. According to the findings of the study, the application of PSAK 106 to musyarakah financing at BRPS Haji Miskin largely adhered to PSAK 106. Nonetheless, there were other aspects of recognition and presentation that need improvement. As cash given to clients is presented as musyarakah financing, musyarakah financing should be recorded as musyarakah investments in a journal. In addition, although the majority of BPRS Haji Miskin's recording has been forwarded to PSAK 106, some transactions still need to be completed, thus the recording is not completed.